Absence of Tuberculosis-Causing Mycobacteria from Slaughtered Livestock Tissues and Environmental Samples, Gauteng Province, South Africa - Vuyokazi Mareledwane; Abiodun A. Adesiyun; Tiny M. Hlokwe (International Journal of Microbiology)
Mycobacterium tuberculosis complex (MTBC) is a group of bacteria responsible for causing tuberculosis in animals and humans. In South Africa (S.A), slaughterhouses are registered by the government and closely inspected and audited for hygienic slaughter practices. Meat inspection to detect lesions has been used for passive surveillance, monitoring, and diagnosis of the disease status. Information on the current status of bovine tuberculosis (bTB) in livestock in the country is limited. Hence, we investigated the occurrence of Mycobacterium spp. in the tissues of slaughtered livestock and environmental samples in abattoirs in Gauteng province of South Africa (S.A). The cross-sectional study employing random sampling from cattle, pigs, and sheep (with the collection of liver, lung, spleen, and different lymph nodes) irrespective of lesions was carried out in 19 red meat abattoirs. Five hundred animals were sampled, comprising cattle (n = 369), pigs (n = 90), and sheep (n = 41). Additionally, 19 environmental samples were collected from feedlots, or where animals drink water while awaiting slaughter, to identify mycobacterial species using culture, acid-fast bacteria staining, and polymerase chain reaction (PCR). The Chi-square and Fisher’s Exact tests were used to detect statistically significant differences in the frequency of detection of Mycobacterium spp. according to the variables investigated (types of tissues, livestock, abattoirs, etc.). The PCR assays detected no MTBC complex species DNA in the bacterial isolates from cattle (n = 32). Sequence analysis (16S rDNA) of the isolates from eight cattle confirmed only two species, namely Mycobacterium colombiense (99.81% identity) and Mycobacterium simiae (99.42% identity). The remaining isolates were identified as members of the Actinomadura species. From the environmental samples, bacterial isolation was made from three samples, and two could only be identified up to the genus level (Mycobacterium species) while the remaining isolate was identified as Mycobacterium senuense (99.22% identity). The study revealed the absence of bovine tuberculosis-causing pathogens in red meat abattoirs of the Gauteng province. Although non-tuberculous Mycobacteria have been implicated as potentially causing tuberculosis-like diseases in livestock, their occurrence in the current study was found to be low, but the potential to cause disease cannot be ignored.